2023
DOI: 10.1038/s41598-023-28839-y
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination status and long COVID symptoms in patients discharged from hospital

Abstract: Effective vaccination against coronavirus mitigates the risk of hospitalisation and mortality; however, it is unclear whether vaccination status influences long COVID symptoms in patients who require hospitalisation. The available evidence is limited to outpatients with mild disease. Here, we evaluated 412 patients (age: 60 ± 16 years, 65% males) consecutively admitted to two Hospitals in Brazil due to confirmed coronavirus disease 2019 (COVID-19). Compared with patients with complete vaccination (n = 185) bef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…Vaccination and increased natural immunity is a likely contributing factor in this decline, and we found lower rates of long COVID coding with increasing vaccination, which is consistent with other studies (18,(58)(59)(60)(61)(62)(63)(64). However, there are methodological limitations in previous work as several studies are small (65)(66)(67) or in self-selecting populations (68)(69)(70)(71) and it is difficult to disentangle the relative contribution of vaccines, variants, and reinfections and how these affect the probability of long-term complications (72)(73)(74)(75).…”
Section: Findings In Contextmentioning
confidence: 99%
“…Vaccination and increased natural immunity is a likely contributing factor in this decline, and we found lower rates of long COVID coding with increasing vaccination, which is consistent with other studies (18,(58)(59)(60)(61)(62)(63)(64). However, there are methodological limitations in previous work as several studies are small (65)(66)(67) or in self-selecting populations (68)(69)(70)(71) and it is difficult to disentangle the relative contribution of vaccines, variants, and reinfections and how these affect the probability of long-term complications (72)(73)(74)(75).…”
Section: Findings In Contextmentioning
confidence: 99%
“…The association between PCC and COVID-19 vaccination before COVID-19 was assessed in 18 studies, including 9 prospective cohorts, 5 retrospective cohorts, 1 case-control study, and 3 cross-sectional studies (Table 1). Fifteen studies stratified their analyses by dosespecific vaccination status (one dose, n = 4; two doses, n = 11; three doses, n = 3) (Supplementary Table S3) and 12 contributed to the meta-analyses (Figures 2 and 3) [23,[28][29][30][31][32][33][34][35][36][37][38].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Nevertheless, post-acute COVID-19 has been observed even among young and middle-aged adults after six to 12 months after mild infection ( Peter et al, 2022 ). Some studies have reported that COVID-19 vaccines had a protective effect against long-COVID even among patients vaccinated before or after SARS-CoV-2 infection/COVID-19 ( Al-Aly et al, 2022 ; Gao et al, 2022 ; Nascimento et al, 2023 ). Additionally, the evidence shows that a SARS-CoV-2 reinfection further increases risks of death, hospitalization, and sequelae in multiple organ systems in the acute and post-acute phase, particularly in those who were unvaccinated and had one vaccination or two or more vaccinations before reinfection ( Bowe et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%